2020
DOI: 10.3389/fpubh.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Culturally- and Linguistically-Adapted Smoking Cessation Text Messaging Intervention for Latino Smokers

Abstract: Objective: Assess the feasibility and acceptability of a culturally- and linguistically-adapted smoking cessation text messaging intervention for Latino smokers. Methods: Using a community-based strategy, 50 Latino smokers were recruited to participate in a smoking cessation pilot study. Participants received a 12-week text messaging intervention and were offered Nicotine Replacement Therapy (NRT) at no cost. We assessed biochemically verified abstinence at 12 weeks, text mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Compared to the study conducted among Latino smokers in the U.S. mainland, participants in this study reported higher self-efficacy for quitting smoking at baseline [ 33 ]. However, it is important to note that in both studies, self-efficacy significantly increased from baseline to Month 3.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Compared to the study conducted among Latino smokers in the U.S. mainland, participants in this study reported higher self-efficacy for quitting smoking at baseline [ 33 ]. However, it is important to note that in both studies, self-efficacy significantly increased from baseline to Month 3.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, participants interacted at higher levels in this study (42.9 text messages per participant). Similar to the studies conducted by Cartujano-Barrera et al and Cupertino et al, participants in this study mostly sent their own, self-composed text messages rather than relying on keywords for a program response [ 31 , 32 , 33 ]. This finding reinforces the hypothesis that text messaging interactivity via keywords may not be sufficient for smoking cessation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations